ESTIMATION OF FILLING PROCESSES IN THE GAS CAP OF GEOSOLITON FIELD - Lubkov, M. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Recently the efficiency of oil-gas deposits exploration has been closely connected with understanding of processes forming of such deposits. In forming, transferring and accumulation processes of hydrocarbons, the important role has mechanism of its vertical migrations. Among models in which such mechanisms were presented, geosoliton conception is well-known enough. Geosoliton conception is in well agreement with many of geologic and cosmogonic ideas. It unites principals of biogenic and abiogenic hypothesis of hydrocarbons forming, which come from mantle in composition of hot high-pressure fluids. The fluids come through the crack-pour faults in the central channel part of geosoliton. The abnormal high pressure of accumulated gases in the central part of geosoliton leads to their penetration in collector reservoirs. At that place deposit geosoliton system is forming. It consists of the gas caps, oil collars and reservoir water in the periphery. Purpose. Estimation of filling processes in the gas cap of geosoliton field. Methodology. To resolve the nonstationary piezoconductivity problem we use combined computer method consisting of variation finite element method and method of finite differences. Findings. As a result of the research, filling process of the gas cap essentially depends on filtration parameters of considering porous reservoir, its size and characteristic fiches of the filling origins. Filling gas cap velocity mainly determined by origins power and less depends on their sizes and quantity. In the subsequent stages of filling, the pressure gradually aligns in all reservoir places and then regularly increases. Originality. Presented method has some advantages in comparison with other similar methods. It enables calculating different reservoir filtration parameters and using manifold boundary conditions. Practical value. The obtained results allow making gas production process in gas-condensate reservoirs more effectively.